Isolation, Synthesis and Characterization of Rosiglitazone Maleate Impurities - Singamsetty Radha Krishna; Mandava Venkata Naga Brahmeshwar Rao; Tirmalaraju Satyanaryana Raju; Vurimidi Himabindu; Ghanta Mahesh Reddy (E-Journal of Chemistry)
Three unknown impurities in rosiglitazone maleate 1 bulk drug at level below 0.1% (ranging from 0.05 to 0.1%) were detected by simple reverse phase high performance liquid chromatography. These impurities were preliminarily identified with LC-MS and characterized by the mass number of the impurities. Different experiments were conducted and finally synthesized and characterized the unknown impurities.